PENILAIAN PELAYANAN AIR BERSIH DI KELURAHAN KEMIJEN KECAMATAN SEMARANG TIMUR - Akmal Ghozali; Nany Yuliastuti (Diponegoro University, 2017)
In Semarang, there are areas of slums that are located in coastal areas and densely populated areas, such as the Village Kemijen in the East Semarang Subdistrict. Based on data of 2014, the slum area in Kemijen Village reached 15.85 Ha. One of the slum problems in this area is inadequate water supply. This study aims to assess the service of clean water in Kelurahan Kemijen. In terms of accommodating the current trend of urban development, that is, community-based development, this study includes community and local organization participation on the clean water provision. The study used quantitative with descriptive analysis method and weighting analysis. This research found that in overall, the condition of clean water facilities and infrastructure and the condition of clean water service are the key elements of clean water provision in this area. Based on the ranking of assessment of clean water service in Kemijen Village, it is known that RW I, II, IV and V are in the lowest rank; then the RW III, VI, VII and IX are in the medium rank, and the RW VIII, X, and XI are included as the area with the best clean water service.